(untitled) (Journal of Business and Technology (Dhaka), 2017)
In this study, the impact of money supply, interest rate and inflation on Dhaka Stock Exchange (DSE) of Bangladesh is explored. These macroeconomic variables are said to have strong impact on capital market. The purpose of this study is to find out if it is true for Dhaka Stock Exchange. For this purpose, data were collected for a period of twelve years from January 2001 to December 2012, on 144 variables. Broad money supply (M2) has been taken as a measure of money supply, 91-days T-bill has been taken as a measure of short-term interest rate and CPI general inflation rate (Base: 1995=100) has been taken as a measure of inflation rate. Apart from that many rules and regulations were reviewed. As to the relationship of the market indices, month-end DGEN Index and its percentage change were used in this paper. A unit root test has been done to see the stationarity of the variables because stationary data are needed for the analysis. A pairwise correlation matrix shows that there was no multicolinearity problem. A simple OLS regression indicates a relationship with money growth, interest rate. But Granger causality test shows that there is only a slight relationship with short term interest rate, nothing else. Overall though a short-run relationship is found between interest rate and market index; the relationship is not very strong. It is proposed that a study estimating long run impact of the explanatory variables should be taken up to know the full effect. Journal of Business and Technology (Dhaka) Vol.11(1-2) 2016; 41-54